The penetration and distribution of topical atropine in animal ocular tissues. Issue 2 (26th September 2018) - Wang, Louis Zizhao; Syn, Nicholas; Li, Shiya; Barathi, Veluchamy Amutha; Tong, Louis; Neo, Jason; Beuerman, Roger W.; Zhou, Lei
Abstract: Purpose: To conduct a multi‐tissue investigation on the penetration and distribution of topical atropine in myopia treatment, and determine if atropine is detectable in the untreated contralateral eye after uniocular instillation. Methods: Nine mature New Zealand white rabbits were evenly divided into three groups. Each group was killed at 5, 24 and 72 hr, respectively, following uniocular instillation of 0.05 ml of 1% atropine. Tissues were sampled after enucleation: conjunctiva, sclera, cornea, iris, ciliary body, lens, retina, aqueous, and vitreous humors. The assay for atropine was performed using liquid chromatography‐mass spectrometry (LC‐MS), and molecular tissue distribution was illustrated using matrix‐assisted laser desorption ionization‐imaging mass spectrometry (MALDI‐IMS) via an independent experiment on murine eyes. Results: At 5 hr, the highest (mean ± SEM) concentration of atropine was detected in the conjunctiva (19.05 ± 5.57 ng/mg, p < 0.05) with a concentration gradient established anteriorly to posteriorly, as supported by MALDI‐IMS. At 24 hr, preferential binding of atropine to posterior ocular tissues occurred, demonstrating a reversal of the initial concentration gradient. Atropine has good ocular bioavailability with concentrations of two magnitudes higher than its binding affinity in most tissues at 3 days. Crossing‐over of atropine to the untreated eye occurred within 5 hr post‐administration. Conclusion: Both transcorneal and transconjunctival‐scleral routes are key in atropine absorption. Posterior ocular tissues could be important sites of action by atropine in myopic reduction. In uniocular atropine trials, cross‐over effects on the placebo eye should be adjusted to enhance results reliability. Combining the use of LC‐MS and MALDI‐IMS can be a viable approach in the study of the ocular pharmacokinetics of atropine.